The Influence of Virtual Reality Media Assisted by Millea Lab on Science Learning on Students' Curiosity and Critical Thinking Skills - Akmala*, Rida; Rosana, Dadan; Anantanukulwong, Roseleena; Gunawan Junaedy, Andri (Jurnal Pendidikan Sains Indonesia, 2025)
Virtual reality (VR) media is a 3D simulation learning medium that can provide direct experience to students by exploring a virtual world that can be felt like real life. VR has advantages, including being able to provide real stimulation about something abstract with the help of electronic devices such as smartphones and VR boxes. The use of VR in education can be done with the help of MilleaLab software. MilleaLab is software that has the advantage of being able to create VR media without coding, already providing audio features, 3D animation, images, Youtube videos, pop-ups, background music (BGM), and quizzes so that it is interesting to use by students. This study was conducted to determine the effect of VR media assisted by MilleaLab on students' curiosity and critical thinking skills (CTS). The method used is a quasi-experiment with a nonequivalent pretest-posttest control group design research design. In the study, the subjects used were two classes, namely the experimental class with learning using VR media assisted by MilleaLab and the control class with learning using Powerpoint. The research data analysis was conducted using the N-Gain test and the Manova test, which had previously conducted the prerequisite test, namely the normality test and the homogeneity test. The results of the study indicate that virtual reality media assisted by MilleaLab has an effect on students' curiosity and CTS. Based on the Manova test, the results of critical thinking have a sig. value of 0.000, and on curiosity, the sig. value of 0.000 indicates that the sig. value 0.05